2019
DOI: 10.12659/msm.914900
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Nomogram for Preoperative Prediction of Perineural Invasion in Colorectal Cancer

Abstract: BackgroundIn colorectal cancer (CRC), perineural invasion (PNI) is usually identified histologically in biopsy or resection specimens and is considered a high-risk feature for recurrence of CRC and is an indicator for adjuvant therapy. Preoperative identification of PNI could help determine the need for adjuvant therapy and the approach to surgical resection. This study aimed to develop and validate a nomogram for the preoperative prediction of PNI in patients with CRC.Material/MethodsA total of 664 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
(28 reference statements)
2
21
0
Order By: Relevance
“…Perineural invasion can occur independently when there is no blood or lymph invasion, and sometimes may be the sole metastasis way for CRC [36]. Perineural invasion is a clinical sign of cancer metastasis and thus signifies the unfavorable prognosis of patients with CRC [37,38]. However, this clinical factor with great prognostic significance has never been explored in patients with EOCRC.…”
Section: Discussionmentioning
confidence: 99%
“…Perineural invasion can occur independently when there is no blood or lymph invasion, and sometimes may be the sole metastasis way for CRC [36]. Perineural invasion is a clinical sign of cancer metastasis and thus signifies the unfavorable prognosis of patients with CRC [37,38]. However, this clinical factor with great prognostic significance has never been explored in patients with EOCRC.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that more than 40 T2D risk prediction models have been established among different populations, there are few risk prediction models based on the East Asian race, especially the Chinese population [ 27 30 ]. Taking into account the genetic and environmental differences (i.e., economic level, diet, climate, and lifestyle), the intensity or distribution of T2D risk factors varies among different populations, complex mathematical formulas, and the lack of simple and intuitive tools to facilitate the use of these predictive risk models [ 14 ]. Therefore, few models are currently used clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…It estimates the regression coefficient by maximizing the logarithmic likelihood function and limits the sum of the absolute values of the regression coefficients [ 13 ]. The regression coefficient estimated by LASSO is very sparse, and many components are exactly 0 [ 14 ]. Therefore, the LASSO automatically removes unnecessary covariates.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, sophisticated and expensive laboratory techniques have limits to their application. Nomograms have been widely used in clinical oncology as reliable tools for estimating numerical probabilities for individual patients by incorporating and illustrating important prognostic factors . This has been demonstrated in several types of cancers, including breast, lung, and gastric cancers, and the predictions of these nomograms may be more accurate than those based on the traditional TNM staging systems for various tumor types .…”
Section: Introductionmentioning
confidence: 99%